Influence of agmatine in adaptation of cAMP signal transduction system of opiate receptors - Li Jin; Li Xin; Pei Gang; Qin Bo-yi (Acta Pharmacologica Sinica, 2016)
AIM: To observe attenuative effects of agmatine on opiate desensitization and substance dependence. METHODS: Guanosine 5'-O-(3-[35S] thiotriphosphate) ([35S]GTTP) binding and cellular cyclic AMP (cAMP) level were determined by radioligand binding assay and radioimmunoassay in NG108-15 cells, respectively. RESULTS: Agmatine increased stimulative action of opioids on [35S]GTTP binding by about 35% and inhibitory effects of opioids on cellular cAMP concentration by about 114.3% in NG108-15 cells pretreated with opioids. On the other hand, it also inhibited cAMP over-shooting by 214.9% of morphine substance dependent cells precipitated by naloxone compared with that of control. These effects of agmatine were antagonized by idazoxan in a concentration-dependent manner. CONCLUSION: Agmatine reversed the formative process of adaptation in cAMP signal transduction cascade.